Breast self-examination: assessing its knowledge attitude and practice among ethnic Kashmiri females - Sideeq, Kouser; Ayoub, Taha; Sailm Khan, S. M. (International Journal Of Community Medicine And Public Health, 2017)
Background: Breast cancer is the most common cancer among women worldwide but is the second commonest cancer in Kashmir women. The most easy and cost effective way of early detection of breast cancer is through breast self-examination (BSE) the utility of which can help to make early interventions and thus better prognosis. The objectives of the study were to assess the knowledge and practice about breast self-examination among ethnic Kashmiri females. Methods: A cross sectional descriptive study was done among ethnic Kashmiri women. A sample 250 women in the age group of 20 to 60 years was selected from SMHS hospital. A predesigned semi-structured study instrument was used to collect the data through interview method. Results: The results showed that only 26% of the participants had ever heard of breast cancer and among them for 50.8% the source of information was media. Regarding knowledge of breast self-examination 92.4 % had never heard of it. Only 5.6% participants had self-examined their breast. Conclusions: The study points to the insufficient knowledge of Kashmiri females about breast cancer and its simplest screening method of self-examination.